Characterization of Pt-Pd/C Electrocatalyst for Methanol Oxidation in Alkaline Medium - S. S. Mahapatra; J. Datta (International Journal of Electrochemistry)
The Pt-Pd/C electrocatalyst was synthesized on graphite substrate by the electrochemical codeposition technique. The physicochemical characterization of the catalyst was done by SEM, XRD, and EDX. The electrochemical characterization of the Pt-Pd/C catalyst for methanol electro-oxidation was studied over a range of NaOH and methanol concentrations using cyclic voltammetry, quasisteady-state polarization, chronoamperometry, and electrochemical impedance spectroscopy. The activity of methanol oxidation increased with pH due to better OH species coverage on the electrode surface. At methanol concentration (>1.0 M), there is no change in the oxidation peak current density because of excess methanol at the electrode surface and/or depletion of OH− at the electrode surface. The Pt-Pd/C catalyst shows good stability and the low value of Tafel slope and charge transfer resistance. The enhanced electrocatalytic activity of the electrodes is ascribed to the synergistic effect of higher electrochemical surface area, preferred OH− adsorption, and ad-atom contribution on the alloyed surface.